2021
DOI: 10.1021/acs.joc.1c00261
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Controlled Regioselective Bromination of 1,2-Disubstituted Cyclobutenes: An Application in the Synthesis of 2,3-Disubstituted Cyclobutenones

Abstract: Easily available disubstituted cyclobutenes were regioselectively halogenated at the allylic position by means of a reaction with bromine. The regioselectivity of bromination is controlled by the presence of a carbocation-stabilizing group. The prepared disubstituted 3-bromocyclobutenes were converted into the corresponding disubstituted cyclobutenones. On the basis of the performed experiments, the mechanism behind the bromination reaction was also proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…An electrocyclic ring opening of this compound produced [4]dendralene 14 – 7 . A similar approach has been employed for the preparation of 2-substituted cyclobutanones [ 82 ] and cyclobutenones [ 83 ]. Further studies have shown that aluminum chloride facilitates the Negishi reaction of cycloalkenyl diphenyl phosphates at room temperature [ 84 , 85 ].…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…An electrocyclic ring opening of this compound produced [4]dendralene 14 – 7 . A similar approach has been employed for the preparation of 2-substituted cyclobutanones [ 82 ] and cyclobutenones [ 83 ]. Further studies have shown that aluminum chloride facilitates the Negishi reaction of cycloalkenyl diphenyl phosphates at room temperature [ 84 , 85 ].…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] On the contrary, the synthesis of cyclobutene-derived boronates and their applications are very scarce. Thus, lithiation of iodo-(1 a) [43] or bromocyclobutene (1 b) [44,45] and subsequent treatment with trialkoxy borates resulted in ionic boronate 2 a, [43] or in neopentyl-protected boronate 2 b after transesterification, [44,45] respectively (Scheme 1, A). The same strategy was used to prepare the simplest cyclobutene derivative 2 c, albeit with moderate overall yield.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Perkow reaction [68], which is based on the reaction of halogenated ketones with phosphites, can also be used to prepare vinyl phosphates (Scheme 2b). This is particularly advantageous for the preparation of triple [69,70] and double [71][72][73][74][75][76] electrophilic templates 6 using brominated ketone 5. Cross-coupling reactions are also useful for the introduction of simple fragmentsnamely, the vinyl group.…”
Section: Introductionmentioning
confidence: 99%